Management of bovine viral diarrhea virus in beef herds - Nickell, Jason S. (Kansas State University, 2010)
Bovine viral diarrhea virus (BVDV) is an endemic pathogen in the U.S. cow herd. The virus can cross the placental barrier and infect the unborn fetus. If infection occurs between 45 – 125 days of gestation, persistent infection (PI) in the unborn fetus is likely. Upon parturition, the PI calf is a lifelong shedder of BVDV significantly elevating the risk of viral exposure to non-PI cattle. Despite reports of significant production loss, many BVDV infections are subclinical and in some cases inconsequential. Our data has highlighted various factors potentially causing disparity in clinical outcomes following BVDV exposure including: variation of BVDV serum concentration among PI cattle which may influence the quantity of virus shed into the environment, preexisting BVDV immune (i.e. antibody) status among non-PI cattle, and the degree of stress experienced by non-PI cattle all may influence the susceptibility of disease. Additionally, cattle transiently infected (TI) with BVDV may temporarily shed BVDV thereby offering another source of exposure to non-PI cattle. Programs focusing on BVDV control and prevention consist of diagnostic tests to identify PI cattle, BVDV vaccines to reduce fetal infection and increase herd immunity, and biosecurity programs intended to prevent BVDV exposure to the resident herd. Survey work performed in Montana suggest that educating beef producers with regard to BVDV has significantly increased the implementation of these tools in order to reduce the risk of introducing BVDV to their resident herd. Despite the risk of production loss, the economic benefit of instituting whole-herd BVDV tests may vary due to herd prevalence. By utilizing Monte Carlo simulation, the current BVDV herd prevalence within the U.S. does not economically justify a nationwide BVDV eradication campaign. However, known BVDV positive herds and herds with an elevated likelihood (47%) of being BVDV positive displayed a positive economic outcome when whole-herd BVDV testing strategies were implemented across herd sizes of 50, 100, and 500 cows. The value of testing various testing modalities was dependent upon herd prevalence and herd size. These data suggest that veterinarians must critically evaluate the value of implementing whole herd testing protocols in U.S. beef herds.
Keywords: Bovine Viral Diarrhea Virus; Cattle; Agriculture, Animal Pathology (0476)